Sustaining the current or pursuing the new: incumbent digital transformation strategies in the financial service industry. A configurational perspective on firm performance - Maik Dehnert (Business Research, 2020)
Digital transformation (DT) is a major challenge for traditional companies. Despite the term, DT is relatively new; its substance is not: a whole stream of research has examined the relationship between DT and firm performance with contradictory findings. Most of these studies have chosen a linear correlational approach, however, did not analyze the holistic interplay of DT dimensions, leading to firm performance. This applies especially to the mature financial services industry and the future perspectives of traditional financial service providers (FSP). Hence, it remains an open question for both research and practice what DT configurations have a positive impact on firm performance. Against this background, the aim of this exploratory study is to examine how DT dimensions are systemically connected to firm performance of incumbent FSP. Drawing on a qualitative-empirical research approach with case data from 83 FSP, we identify digital configurations along different levels of firm performance. Our findings suggest an evolution of digital configurations of FSP, leading to five empirical standard types from which only one managed to establish a profound basis of DT.
Keywords: 650; Digital transformation; Banking; Insurance; Financialservices; Configurational analysis; fsQCA